EFEKTIVITAS PELAYANAN MASYARAKAT DI KANTOR KELURAHAN MUNGKU BARU KECAMATAN RAKUMPIT KOTA PALANGKA RAYA - Purnamasari; Ricky Zulfauzan; Wijoko Lertariono (Jurusan Ilmu Pemerintahan, 2021)
This study aims to determine and explain the effectiveness of community services at the Mungku Baru Village Office, Rakumpit District and to find out and explain what are the supporters and obstacles in community service at the Mungku Baru Village Office, Rakumpit District. The data collection method used in this study is the Documentation, Observation and Interview method. The results of the study were analyzed through descriptive methods describing how the level of effectiveness of community services in Mungku Baru Village, Rakumpit District, Palangka Raya City and the inhibiting and supporting factors of service effectiveness, the data used in this study is primary data and secondary data with research subjects consisting of the Mungku Baru Village Government, the Mungku Baru Village Office and the Mungku Baru Village community. The results showed that the effectiveness of community services in Mungku Baru Village, Rakumpit District, Palangka Raya City, researchers saw the success that showed the extent to which the plan could be achieved. The more plans that can be achieved, the more effective the activity will be, so that the word effectiveness can also be interpreted as the level of success that can be achieved from a certain method or effort in accordance with the objectives to be achieved. With benchmarks using the theory of Gibson 2013 (a) Clarity of Goals Achieved. (b) Clarity of Strategy for Achievement of Goals. (c) Careful Planning. (d) Proper Programming. (d) Availability of facilities and infrastructure. The researcher concludes that Mungku Baru Village, Rakumpit District, in this case the effectiveness of community services in Mungku Baru Village, Rakumpit District, Palangka Raya City is still less effective for the community. The supporting and inhibiting factors of Service Effectiveness for the Mungku Baru community, namely Human Resources (HR) who are capable of adequate, professional work and facilities and infrastructure to be able to support the continuity of services. In addition, community empowerment is also very important and is something that must be done considering the rapid economic and technological growth in recent times.